Assessment of the Decontamination and Disinfecting Potentials of Ocimum gratissimum Synthesized Silver Nanoparticles on Water and Wastewater Samples (IPS Journal of Public Health, 2023)
The presence of organic, inorganic and biological pollutants in natural water supply are the major indices of water pollution. The application of green nanoparticles in water treatment is one of the promising ways of eradicating these pollutants and providing safe and quality water for domestic, agricultural and industrial purposes. Our research was intended to evaluate the decontamination and disinfecting potentials of Ocimum gratissimum silver nanoparticles on water and wastewater samples. The green silver nanoparticles were formed using aqueous O. gratissimum leaf extract and characterized using standard nanotechnological techniques while decontamination and disinfecting potentials of the green silver nanoparticles were examined through physicochemical, heavy metal and bacteriological analysis. The results revealed the spectral and morphological profiles were in conformity with the characteristics of silver nanocrystals. There were significant reductions (P < 0.05) in physicochemical, heavy metal and bacterial qualities of the four water samples at higher (0.5 mg/L) and lower (0.25 mg/L) doses of the green silver nanoparticles and their decontamination and disinfection efficiencies were comparable to the positive control calcium hypochlorite. These findings suggest that O. gratissimum silver nanoparticles could be exploited in restoring the quality of water and wastewater.
Keywords: C. papaya; Decontamination; Disinfection; Silver nanoparticle; Water quality